Factors influencing the choice of caesarean delivery and their satisfaction among pregnant women attending maternity hospital in Eastern Uttar Pradesh - Khan, Imran Ahmed; Tiwari, Harish Chandra; Malik, Najma (Indian Journal of Community Health, 2023)
Introduction: The birth of a baby through the vaginal route is a traditional way of delivery. But, at times normal vaginal delivery is not desirable due to various reasons. Under such circumstances, Lower section caesarean section (LSCS) is carried out to deliver the baby safely. There are rising concerns about the increasing rate of caesarean sections with wide variations in rates across the globe. Factors that influence the decision to perform a LSCS are often complex and multifactorial. Understanding these complexities is one of many steps to help stop the rise of any unnecessary LSCSs or prevent their over-use. Aim: To find out factors influencing the choice of caesarean delivery among recently delivered mothers through caesarean section and within puerperium. Method: A cross-sectional survey using pretested, self-administered, semi-structured questionnaire was done between December 2022 to February 2023 among patients recently delivered through caesarean section and within puerperium. Result: A total of 250 participants were approached over a three-month period. Among them, 211 completed the survey. The majority of participants were in the age group 25 to 30 years, Hindu by religion, and residents of rural areas. Sixty-four participants perceived that LSCS was done for the safety of the baby. Educational status (p<0.001), place of previous delivery (p<0.001), and count of current LSCS (p=0.016) were the factors associated with caesarean delivery satisfaction and it was found to be statistically significant. Conclusion: About one-third of the participants perceived that LSCS was done for the safety of the baby. The majority of participants were satisfied with the decision of LSCS.